Perubahan Sosial Budaya Masyarakat di Sekitar Kawasan Wisata Pulo Cinta Eco Resort - Annisa Rizqa Alamri; Yayan Hanapi (JURNAL MASTER PARIWISATA, 2021)
A meeting between the local community and tourists will produce some social changes in the local community where tourist site is located. The present study describes forms of socio-cultural changes in the local communities since the formation of Pulo Cinta Eco Resort for four years. The purpose of the present study was to examine the forms of socio-cultural changes in Patoameme Village community after the development of Pulo Cinta Eco Resort. The research method was case study using descriptive approach. This was based on the issues, which were what the object was and how it was formed. The data collection used observation, in-depth interview, and document study. The data was analyzed by performing data reduction, display and conclusion drawing. The data validity was examined using data source triangulation technique. Based on the findings in the field, the socio-cultural changes were; 1) symbols, b) language, c) values and d) norms. Keywords: Social Cultural Changes, Develepoment of Tourist Areas, Local Community